Mobilizing cultural supports against the commercial sexual exploitation of (female) children (CSEC) in Solomon Islands community development. Issue 3 (27th May 2019) - Thompson, Lester; Tupe, Linda; Wadley, David; Flanagan, Karen
ABSTRACT: As reflected in the Pacific nation of Solomon Islands (SI), child trafficking and the commercial sexual exploitation of children (CSEC) represent global problems with serious ramifications for community development. While acknowledging the deployment of internationalist, "child rights" interventions combined with top-down legislative provisions, this article revisits the possibility of positive, community-based strategies. Having appraised problematic contexts of the SI economy, society, and culture, it advances a comprehensive theoretical platform to facilitate a practice approach using customary and local measures to foster the status of women and children, counter CSEC, and advance community relations. Explained at both national and local scales, the methodology is presented for review prior to implementation. If successful, it is likely to have wide application in other afflicted societies.